Antarctic Wide Subglacial Hydrology Modeling - Shivani Ehrenfeucht; Christine Dow; Koi McArthur; Mathieu Morlighem; Felicity S. McCormack (Geophysical Research Letters)
Abstract Global sea levels are rising due, in large part, to the increase in the rate of melting of ice sheets as a direct result of climate change. A large fraction of uncertainty in future sea level rise comes from limited understanding of basal conditions under ice sheets. Specifically, subglacial hydrology, which describes the volume and movement of meltwater underneath glaciers and resulting basal water pressures. This system exerts a strong control on ice basal sliding and the rate of ice shelf melt, both of which can destabilize glaciers and lead to enhanced sea level rise. Here, we present subglacial hydrology model results of the full Antarctic Ice Sheet derived using the Glacier Drainage System model. We examine water pressures of the distributed drainage system, the distribution of the channelized system, and freshwater discharge across grounding lines of major drainage basins in the steady state subglacial system under present day conditions.